Trypanosoma cruzi Promotes Transcriptomic Remodeling of the JAK/STAT Signaling and Cell Cycle Pathways in Myoblasts - Nisimura, Lindice M.; Coelho, Laura L.; de Melo, Tatiana G.; Vieira, Paloma de Carvalho; Victorino, Pedro H.; Garzoni, Luciana R.; Spray, David C.; Iacobas, Dumitru A.; Iacobas, Sanda; Tanowitz, Herbert B.; Adesse, Daniel (Frontiers in Cellular and Infection Microbiology, 2020)
Chagas disease is responsible for more than 10,000 deaths per year and about 6 to 7 million infected people worldwide. In its chronic stage, patients can develop mega-colon, mega-esophagus, and cardiomyopathy. Differences in clinical outcomes may be determined, in part, by the genetic background of the parasite that causes Chagas disease. Trypanosoma cruzi has a high genetic diversity and each group of strains may elicit specific pathological responses in the host. Conflicting results have been reported in studies using various combinations of mammalian host – T. cruzi strains. We previously profiled the transcriptomic signatures resulting from infection of L6E9 rat myoblasts with four reference strains of T. cruzi (Brazil, CL, Y and Tulahuen). The four strains induced similar overall gene expression alterations in the myoblasts, although only 21 genes were equally affected by all strains. Cardiotrophin-like cytokine factor 1 (Clcf1) was one of the genes found to be consistently up-regulated by the infection with all four strains of T. cruzi. This cytokine is a member of the interleukin-6 family that binds to glycoprotein130 receptor and activates the JAK-STAT signaling pathway, which may lead to muscle cell hypertrophy. Another commonly upregulated gene was tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein theta (Ywhaq, 14-3-3 protein Ɵ), present in the Cell Cycle Pathway. In the present work, we re-analyzed our previous microarray dataset, aiming at understanding in more details the transcriptomic impact that each strain has on JAK-STAT signaling and Cell Cycle pathways. Using Pearson correlation analysis between the expression levels of gene pairs in biological replicas from each pathway, we determined the coordination between such pairs in each experimental condition and the predicted protein interactions between the significantly altered genes by each strain. We found that although these highlighted genes were similarly affected by all four strains, the downstream genes or their interaction partners were not necessarily equally affected, thus reinforcing the idea of the role of parasite background on host cell transcriptome. These new analyses provide further evidence to the mechanistic understanding of how distinct T. cruzi strains lead to diverse remodeling of host cell transcriptome.